Subglottic hemangioma can be missed: Two case reports - Shahd M. Alsaqoub; Sara G. Almutairi; Samir M. Bawazir; Wala S. Alshiha; Mohammed S. Halawani; Jaber Alshammari (Elsevier, 2019)
We report 2 cases of infants with subglottic hemangioma, in which the diagnosis was later discovered. These two infants had initially presented with stridor. They were both thoroughly investigated, but no abnormality was found after different procedures and investigations. Later, a subglottic hemangioma was seen during direct laryngobronchoscopy in the first infant. The second infant underwent multiple direct laryngobronchoscopies that were unremarkable, but the last one showed a blue rubber mass covered by normal mucosa in the subglottic area. A CT scan of the neck with contrast confirmed the diagnosis of subglottic hemangioma. A high index of suspicion is needed in subglottic hemangioma, as late diagnosis can lead to a higher mortality rate. Sometimes, serial direct laryngobronchoscopies cannot establish a diagnosis; however contrasted CT scans can aid in the diagnosis. Keywords: Hemangioma, Laryngeal neoplasms, CT scan